The Development of Flipbook Based E-Module with a Project Based Learning Model In The Subject of Electricity and Electronics - Rahmi, Salsabila Tri; Nursyafti, Yolana; Purwanto, Wawan; maksum, Hasan; Hendriyani, Yeka (PAKAR Pendidikan, 2023)
Developments in the 4.0 era at this time require us to be able to use science and technology as much as possible to think creatively, be innovative and be able to solve existing problems. One way education can keep up with this era is by including technology in the learning process. Modules developed in electronic form can be a solution to answer this problem. In addition to teaching modules as learning media, learning models are no less important in supporting learning effectiveness. One learning model that facilitates students applying learning material through an experiment and project is the Project Based Learning (PjBL) learning model. Flipbook-based e-modules with the Project Based Learning learning model are conventional modules that are converted into electronic form using the Flip PDF Professional application so that they can be used anytime and anywhere. The type of research used is Research and development with a 4D model (define, design, develop, and disseminate). The research was conducted at the Department of Automotive Engineering, Padang State University in the subject of electricity and electronics. The results of this study found that the e-module was declared valid both in terms of media and material from each validator. Lecturers and students also provide an assessment of the practicality of the flipbook-based e-module with this project-based learning model with an average percentage of 88.9% in the very practical category. This flipbook-based e-module is declared effective to use. This was obtained from the results of the students' classical completeness after carrying out the posttest with a percentage of 87.5% and a gain score of 0.47 in the moderate category.